Optimizing Fin Parameters to Enhance Passive Heat Dissipation in Photovoltaic Panels - Nisha Gupta; Dr. Dinesh Kumar Koli (International Journal of Radio Frequency Innovations, 2024)
This study explores passive cooling techniques to enhance the thermal management of photovoltaic (PV) modules, which is crucial for maintaining efficiency. A computational fluid dynamics (CFD) model, using ANSYS Fluent, was developed to evaluate three fin shapes: rectangular, trapezoidal, and triangular, attached to the back of PV modules. The study varied parameters such as fin count, thickness, and length to determine optimal configurations for cooling. Among the designs, triangular fins demonstrated the highest cooling efficiency, achieving a temperature reduction of 5.3% for a 30 mm length and 4.85% for a 60 mm length. Trapezoidal fins also effectively reduced temperatures, with improvements up to 7.05%. The findings suggest that enhancing fin thickness and quantity can further optimize cooling, with triangular and trapezoidal designs outperforming rectangular fins. These insights indicate that carefully designed fin configurations can meaningfully improve PV performance by reducing operating temperatures, thus aiding in sustainable energy production. Photovoltaic (PV) panels' efficiency is highly sensitive to temperature; higher operating temperatures result in reduced energy conversion efficiency and a shorter lifespan. Fin-based systems and other passive cooling methods offer a sustainable way to dissipate heat efficiently without relying on external electricity. This article examines the optimization of fin characteristics to enhance the passive heat dissipation of PV panels. Key elements such as fin geometry, material selection, and spatial arrangement are analyzed to identify ways to optimize heat transfer. The effect of optimized fin designs on PV panel performance is demonstrated through a review of experimental findings and computational simulations. The importance of optimized fins in sustainable energy solutions is emphasised in this article's conclusion, which also discusses potential future developments.
Keywords: PV efficiency; Passive cooling; Photovoltaic module cooling; fin design; heat dissipation; simulation model; temperature reduction; trapezoidal fins; triangular fins